Targeting the restricted α-subunit repertoire of airway smooth muscle GABA(A) receptors augments airway smooth muscle relaxation - Gallos, George (American Physiological Society, 2012)
The prevalence of asthma has taken on pandemic proportions. Since this disease predisposes patients to severe acute airway constriction, novel mechanisms capable of promoting airway smooth muscle relaxation would be clinically valuable. We have recently demonstrated that activation of endogenous airway smooth muscle GABA(A) receptors potentiates β-adrenoceptor-mediated relaxation, and molecular analysis of airway smooth muscle reveals that the α-subunit component of these GABA(A) receptors is limited to the α(4)- and α(5)-subunits. We questioned whether ligands with selective affinity for these GABA(A) receptors could promote relaxation of airway smooth muscle. RT-PCR analysis of GABA(A) receptor subunits was performed on RNA isolated by laser capture microdissection from human and guinea pig airway smooth muscle. Membrane potential and chloride-mediated current were measured in response to GABA(A) subunit-selective agonists in cultured human airway smooth muscle cells. Functional relaxation of precontracted guinea pig tracheal rings was assessed in the absence and presence of the α(4)-subunit-selective GABA(A) receptor agonists: gaboxadol, taurine, and a novel 8-methoxy imidazobenzodiazepine (CM-D-45). Only messenger RNA encoding the α(4)- and α(5)-GABA(A) receptor subunits was identified in RNA isolated by laser capture dissection from guinea pig and human airway smooth muscle tissues. Activation of airway smooth muscle GABA(A) receptors with agonists selective for these subunits resulted in appropriate membrane potential changes and chloride currents and promoted relaxation of airway smooth muscle. In conclusion, selective subunit targeting of endogenous airway smooth muscle-specific GABA(A) receptors may represent a novel therapeutic option for patients in severe bronchospasm.